Introduction to architectural technology. - Silver, Peter, ....- (London : Laurence King, 2008)
Introduction to Architectural Technology, by Pete Silver and Will McLean and published by Laurence King in October 2008 is aimed at architectural students and provides an accessible introduction to all aspects of architectural technology: structural physics, structural elements and forms, heating, lighting, environmental control, and computer modelling. As well as providing a clear grounding in these topics, it will also help students to integrate their design thinking with appropriate structural and environmental solutions. The book sets out to explain the relationships between physical phenomena, materials, building elements and structural types using simple classification systems and real world examples. Photographs are used to familiarise the user with common construction technology, while historical examples are employed to chart significant moments in the history of architectural engineering. Every topic area is accompanied by a set of cross-references for further reading and research.
Structure and form - structural physics - structural elements - structural logic - climate and shelter - human comfort - building performances - computational tools and techniques - case studies - building codes.
Keywords: Bouwkunde